Home Visits for Prevention of Impairment and Death in Older Adults: A Systematic Review. Issue 1 (1st May 2014) - Grant, Sean; Parsons, Amanda; Burton, Jennifer; Montgomery, Paul; Underhill, Kristen; Wilson, Evan Mayo; Macdonald, Geraldine; Huband, Nick; Wilson, Joanne; Dennis, Jane
Executive summary: "This Campbell systematic review assesses the effectiveness of home visits in preventing impairment, institutionalization, and death in older adults, as well as identifying factors that may moderate effects. The review summarises findings from 64 studies. Overall, home visits are not effective in maintaining the health and autonomy of community‐dwelling older adults. Preventive home visits did not reduce absolute mortality, and did not have a significant overall effect on the number of people who were institutionalised. There is high‐quality evidence of no effect on falls from interventions targeting fall prevention. There is low‐quality evidence of small statistically significant positive effects for functioning and quality of life. It is possible that some programmes have modest effects on institutionalisation and hospitalisation. However, heterogeneity in target population and intervention design, as well as poor reporting of in studies of design, implementation and the control condition make this difficult to determine." BACKGROUND: Home visits by health and social care professionals aim to prevent cognitive and functional impairment, thus reducing institutionalisation and prolonging life. Visitors may provide health information, investigate untreated or sub‐optimally treated problems, encourage compliance with medical care, and provide referrals to services. Previous reviews have reached varying conclusions about their effectiveness. This review sought to assess the effectiveness of preventive home visits for older adults (65+ years) and to identify factors that may moderate effects. OBJECTIVES: To systematically review evidence on the effectiveness of preventive home visits for older adults, and to identify factors that may moderate effects. SEARCH STRATEGY: We searched the following electronic databases through December 2012 without language restrictions: British Nursing Index and Archive, C2‐SPECTR, CINAHL, CENTRAL, EMBASE, IBSS, Medline, Nursing Full Text Plus, PsycINFO, and Sociological Abstracts. Reference lists from previous reviews and from included studies were also examined. SELECTION CRITERIA: We included randomised controlled trials enrolling persons without dementia aged over 65 years and living at home. Interventions included visits at home by a health or social care professional that were not directly related to recent hospital discharge. Interventions were compared to usual care, wait‐list, or attention controls. DATA COLLECTION AND ANALYSIS: Two authors independently extracted data from included studies in pre‐specified domains, assessed risk of bias using the Cochrane Risk of Bias tool, and rated the quality of evidence using GRADE criteria. Outcomes were pooled using random effects models. We analyzed effects on mortality, institutionalization, hospitalization, falls, injuries, physical functioning, cognitive functioning, quality of life, and psychiatric illness. RESULTS: Sixty‐four studies with 28642 participants were included. There was high quality evidence that home visits did not reduce absolute mortality at longest follow‐up (Risk ratio=0.93 [0.87 to 0.99]; Risk difference=0.00 [‐0.01 to 0.00]). There was moderate quality evidence of no clinically or statistically significant overall effect on the number of people who were institutionalised (Risk ratio=1.02 [0.88, 1.18]) or hospitalised (Risk ratio=0.96 [0.91, 1.01]) during the studies. There was high quality evidence of no statistically significant effect on the number of people who fell (Odds ratio=0.86 [0.73, 1.01]). There was low quality evidence of statistically significant effects for quality of life (Standardised mean difference=‐0.06 [‐0.11, ‐0.01]) and very low quality evidence of statistically significant effects for functioning (SMD=‐0.10 [‐0.17, ‐0.03]), but these overall effects may not be clinically significant. However, there was heterogeneity in settings, types of visitor, focus of visits, and control groups. We cannot exclude the possibility that some programmes were associated with meaningful benefits. AUTHORS' CONCLUSIONS: We were unable to identify reliable effects of home visits overall or in any subset of the studies in this review. It is possible that some home visiting programmes have beneficial effects for community‐dwelling older adults, but poor reporting of how interventions and comparisons were implemented prevents more robust conclusions. While it is difficult to draw firm conclusions given these limitations, estimates of treatment effects are statistically precise, and further small studies of multi‐component interventions compared with usual care would be unlikely to change the conclusions of this review. If researchers continue to evaluate these types of interventions, they should begin with a clear theory of change, clearly describe the programme theory of change and implementation, and report all outcomes measured.